Composting: A Better Solution for Managing Nepal’s Increasing Solid Waste - Lohani, Shreesti Raj (Journal of the Institute of Engineering, 2018)
In developing countries like ours, environmental factors are not given that priority while managing solid waste. Poor planning and management is continuously resulting to environmental degradation and ecological imbalance. Composting, which is a traditional yet sustainable and environment friendly way of managing solid waste is being neglected. In this article, I have first tried to put forward the existing situation of waste management and waste disposal practices in our county and then to explain about how composting is being practiced in today’s scenario. I made field study in Sawal Bahal and Teku area and also referred to published information for this paper. I have tried to highlight the fact that composting, with a little effort from government side and each individual involved, it can prove to be a very effective means of managing solid waste. This practice will definitely help to boost the economic activities of the country. The later part of the paper explains the benefits of composting for each individual level to national level. Various factors whether it be environmental upgradation to new job opportunities or for best agricultural practices, composting can prove beneficial for all. Journal of the Institute of Engineering, 2017, 13(1): 215-220